Improving child nutrition and development through preschools in Malawi - Gelli, Aulo; Margolies, Amy; Santacroce, Marco; Twalibu, Aisha; Roschnik, Natalie; Chidalengwa, George; Phiri, Peter; Moestue, Helen; Katundu, Mangani (International Food Policy Research Institute, 2019)
Some 12,000 community preschools in Malawi serve 45 percent of the county’s preschool population. Yet because of food insecurity and communities’ difficulties in providing preschoolers with a midmorning meal, these schools may not survive. To address this challenge, Save the Children and the University of Malawi’s Chancellor College designed a preschool-based nutrition and agriculture intervention aimed at helping rural communities to produce and prepare more nutritious foods for preschools and for households year-round. An IFPRI-led cluster-randomized controlled trial in 60 preschools in the southeastern district of Zomba found that after just one year of the intervention, agricultural production, the quality and frequency of preschool meals, and household and child dietary diversity had all improved. The intervention also had an impact on the diets and growth of the preschoolers’ younger siblings. These results suggest that preschools can provide an effective platform for scaling-up nutrition and agriculture interventions, benefiting not only the preschools but also communities, households, and children in their first 1,000 days.